Distinct iron homeostasis in C57BL/6 and Balb/c mouse strains. Issue 9 (8th May 2020) - Saha, Piu; Xiao, Xia; Li, Yaqi; Golonka, Rachel M.; Abokor, Ahmed A.; Yeoh, Beng San; Vijay‐Kumar, Matam
Abstract: C57BL/6 (BL6) and Balb/c mice exhibit prototypical Th1‐ and Th2‐dominant immune predispositions, respectively. Iron is a proinflammatory metal ion; however, limited information is documented on the differences in iron homeostasis between BL6 and Balb/c strains. The objective of this study was to investigate the extent to which strain‐level differences in these mice dictates the regulation of iron homeostasis during physiologic and inflammatory conditions. At basal levels, Balb/c mice displayed significantly higher levels of iron in systemic circulation and tissue compared to BL6 mice. Moreover, Balb/c mice had greater iron absorption as indicated by higher gene expressions of duodenal DcytB, DMT1, Fpn, SFT, and Heph . Similarly, hepatic Tf, TfR1, TfR2, and DMT1 expressions were augmented in Balb/c mice. Interestingly, there was no change in hepatic Hamp expression between the two strains, suggesting that the disparity in their maintenance of iron is independent of hepcidin. Additionally, the basal levels of intracellular labile iron pool in Balb/c intestinal epithelial cells, and bone marrow‐derived macrophages and neutrophils, were higher compared to BL6 mice. When mice were challenged with lipopolysaccharide, the acute inflammatory response in BL6 mice was more pronounced than in Balb/c mice, as indicated by the more rapid development of hypoferremia and upregulation of serum IL‐6 and TNF‐ α levels in BL6 mice. In conclusion, this study underscores that iron homeostasis is distinct between BL6 and Balb/c strains under both physiologic and inflammatory conditions. Abstract : Relative to C57BL/6 mice (BL6), Balb/c mice harbor more circulating, tissue and labile iron pool (LIP), which correlates with their generally heightened expression of key iron‐regulatory proteins like divalent metal transporter 1 (DMT1) andferroportin. Accordingly, such strain‐level differences in iron homeostasis could explain the dissimilar degree of developing pro‐inflammatory responses, followed by hypoferremia, in response to inflammatory challenge like lipopolysaccharides (LPS), which occurs more rapidly in BL6 mice than Balb/c mice.